PENENTUAN KEWAJIBAN SUAMI DALAM MEMBERIKAN NAFKAH PASCA PERCERAIAN (MUT’AH) DI PENGADILAN AGAMA KOTA TASIKMALAYA : (ANALISIS PUTUSAN NOMOR: 0655/PDT.G/2016/PA.TMK) - Hamim, Mohamad (Program Studi Hukum Keluarga Islam, 2025)
Divorce is a legal action that appears a series of consequence law. In talaq, there is primarily an obligation for x-husband to give mut’ah, iddah, mahr (dowry) if it had not been paid, support his child financially as well. The problem will be discussed in this study is : firstly, the concept of mut’ah determination, iddah, and child financial are based on islamic law and Indonesian Government Regulation. Secondly, consideration of the judges of Tasikmalaya religious court in granting the file of husband financial obligation post-divorce. The last, there is compatibility between desicion number: 0655/Pdt.G/2016/PA.Tmk with islamic law. The result of this study is husband financial obligation post-divorce is filed by the respondent (x-wife) that is contained in rekonvensi. In talaq, a wife can file rekonvensi, it means counterclaim. Eventhough she does not want it, it does not matter because there is no necessity about it whereas ex officio right, the judges only can determine mut’ah and iddah. The judges can make a decision from proof and fact in court. They make a decision about amount of mut’ah, iddah, and child financial are influenced by three factors, they are : husband ability of net wage, wife elegibility of maskan, kiswah, mat’am ,and the parties (husband and wife) appropriateness of economic condition when they married and others are length of marriage and economic condition around their residence. Conformity of the judges decision at Tasikmalaya Religious Court has agreed with Indonesian Government Regulation.